2010
DOI: 10.5152/akd.2010.158
|View full text |Cite
|
Sign up to set email alerts
|

The relation between exercise- induced myocardial ischemia and high-sensitive C-reactive protein and neopterin levels

Abstract: ÖZETAmaç: Yüksek duyarlılıklı C-reaktif protein (hsCRP) ve neopterin, ateroskleroz gelişimi ile ilişkilidir. Bu çalışmada kararlı anjina pektorisli (KAP) hastalarda, egzersiz stres testi (EST) esnasında oluşan miyokart iskemisi ile hsCRP ve neopterin seviyeleri arasındaki ilişki ve EST ile hsCRP ve neopterin düzeylerinde meydana gelen değişimin tıkayıcı koroner lezyon varlığını öngörmedeki yeri araştırılmıştır. Yöntemler: Çalışmamız prospektif, gözlemsel olarak dizayn edildi. Çalışmaya KAP ile takip edilen 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A study in Turkey reported that after exercise stress test there was a significant increase of 0.5 mg/L of post-exercise stress test hs-CRP level over the baseline in subjects with obstructive coronary lesions, while there was no increase in subjects without obstructive coronary lesions. (31) The study in Turtu concluded exercise induced a significant increment in inflammatory markers i.e., white blood count, hs-CRP, IL-6, IL-10 and MCP-1 concentrations. The long-distance sculling intensity variables such as the average rating of perceived exertion, HR and blood lactate were correlated with changes in IL-8, IL-1α and IL-1β levels.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Turkey reported that after exercise stress test there was a significant increase of 0.5 mg/L of post-exercise stress test hs-CRP level over the baseline in subjects with obstructive coronary lesions, while there was no increase in subjects without obstructive coronary lesions. (31) The study in Turtu concluded exercise induced a significant increment in inflammatory markers i.e., white blood count, hs-CRP, IL-6, IL-10 and MCP-1 concentrations. The long-distance sculling intensity variables such as the average rating of perceived exertion, HR and blood lactate were correlated with changes in IL-8, IL-1α and IL-1β levels.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional criterion for the detection of myocardial ischemia is the development of ST‐segment depression or elevation during the test; however, the diagnostic value of this criterion is limited because of its relatively low sensitivity. To improve the identification of myocardial ischemia with this modality, various parameters, such as P‐wave duration, hs‐CRP elevation, ST elevation in aVR derivation, abnormal heart rate recovery, troponin, and NT‐pro‐BNP‐levels with ST‐segment depression or copeptin level have recently been suggested …”
Section: Introductionmentioning
confidence: 99%